The Portrait of Social Capital and Conflict Reconciliation for Peace in Sunni-Shia Relationships: Evidence from Sampang Madura, Indonesia - ., Maskuri; Mustafida, Fita; Andriyansyah, M. Fahrudin (Journal of Ecohumanism, 2025)
The sectarian conflict between Sunni and Shia communities in Sampang led to the forced relocation of Shia residents to the Puspa Agro Jumundo Sidoarjo flats. Despite various reconciliation efforts to reintegrate displaced Shia residents into their homeland, there remains a lack of research focusing on the reconciliation process and the active participation of diverse stakeholders in fostering peace. This study addresses this gap through an ethnographic design, providing in-depth insights into the reconciliation process by immersing in the lived experiences of Sunni and Shia residents and the key participants involved in the peacebuilding efforts. Using ethnographic methods, this research examines the perspectives of critical stakeholders, including the village head (Klebun), hamlet head, Team 5, the Village Consultative Body (BPD), Islamic organizations such as the Nahdlatul Ulama' Karang Penang branch, local government officials (e.g., the Regent of Sampang), and both displaced and returning Shia residents. Through prolonged engagement and participant observation, the study captures the complex social interactions, cultural practices, and narratives that shape the reconciliation process. The findings reveal the fragmented brotherhood in Sampang caused by sectarian divisions rooted in differing fundamental values between Shia teachings and the long-standing traditions of the local Sunni community. The study highlights the critical role of Sampang's religious and social culture in shaping the reconciliation process. These cultural elements serve as vital sources of strength and social capital, facilitating dialogue and rebuilding trust. By employing an ethnographic lens, this research offers novel insights into the dynamics of peacebuilding in sectarian conflicts. It provides a deeper understanding of how local traditions, social structures, and cultural practices can be leveraged to resolve communal tensions and foster sustainable reconciliation.